Seeking a Culturally Relevant Ethic of Care for Mexican/Mexican American Youth: a revolucionista ethic of care and its wily, tactical mechanism of humor - Mia Angélica Sosa-Provencio (Journal of Philosophical Investigations)
Black and Latina female educators have for centuries prepared children of color to resist dehumanization, claim full citizenship, and transform oppression through culturally specific Critical Feminist Ethics of Care. In 2018, I detailed a Revolucionista Ethic of Care specific to the needs and strengths of Mexican/Mexican American (Mexicanx/a/o) youth which offers a subterraneous social justice ethic of care through the curriculum and pedagogy of four female Spanish-speaking New Mexican (Nuevomexicana) and Mexican American (Mexicana) educators. Through this land-based Chicana Feminist Testimonio Methodology, I unearth a resistant, healing Critical Feminist Ethic of Care framework for (Nuevo)Mexicana/o children and communities which enriches the field of Care scholarship through its embodied, land-based epistemologies. I explore the ways in which four (Nuevo)Mexicana educators operationalize play and humor within their Ethic of Care to 1) open access to a mythic time/space continuum wherein they may access the historical and ongoing wounds of injustice fueling them, 2) gleefully travel to students’ multiple worlds, and 3) forge liminal spaces of joy for Mexicanx/a/o youth to shape futures of thriving. This work offers ancient, practiced tools of resistance and healing in this new and yet historicized moment of racialized hostility and hate against Communities of Color in the United States.